Positivity statements for a mixed-element-volume scheme on xed and moving grids - Cournède, Paul-Henry; Koobus, Bruno; Dervieux, Alain (European Journal of Computational Mechanics, 2006)
This paper considers a class of second-order accurate vertex-centered mixed niteelement nite-volume MUSCL schemes. These schemes apply to unstructured triangulations and tetrahedrizations and uxes are computed on an edge basis. We dene conditions under which these schemes satisfy a density-positivity statement for Euler ows, a maximum principle for a scalar conservation law and a multicomponent ow. This extends to an Arbitrary- Lagrangian-Eulerian formulation. Steady and unsteady ow simulations illustrate the accuracy and the robustness of these schemes.